RELATIONSHIP BETWEEN GAIT DEVIATIONS AND RISK OF FALLS IN PATIENTS WITH TYPE 2 DIABETES - Bweir, Salameh (European Scientific Journal, ESJ, 2014)
Diabetes mellitus (DM) is a major cause of morbidity. It is an epidemic that affects more than 300 million people worldwide. Elderly Individuals with DM are expected to be more prone to fall for reasons such as sensorimotor functions impairment, musculoskeletal limitation, joints pain, and pharmacological complications. The aim of this study is to find the relationship of gait deviations and risk of fall in community- dwelling DM patient with neuropathy and high HbA1c. Method: Fifteen male elderly subjects with type 2 DM, neuropathy and HbA1c >7, fifteen elderly male subjects with no DM, matched age average for both groups were 66 years. Both groups were evaluated for gait deviation using 4 digital cameras and digitally measure stride length and step width. Risk of fall was assisted using TUG test. Results: The results showed significant difference between groups in steps width, strides length and TUG test with P >0.05. There was a significant strong negative correlation between the HbA1c and Stride Length (r = -0.810, p = 0.000). There was a significant strong positive correlation between the HbA1c and Step Width (r = 0.759, p = 0.001). However, there was a nonsignificant weak positive correlation between the HbA1c and TUG test (r = 0.482, p = 0.069). Conclusion Diabetic subjects with neuropathy are having gait deviations that significantly correlated with risk of fall. That indicates the need for fall prevention programs for diabetic population, and more care to correct for gait deviations to lower the risk of falls.